A polythiol composition and its preparation method and application
By controlling the content of the cyclic compound in the polythiol composition, the problems of uneven color and high defect rate of lenses are solved, and the high quality preparation of lenses is achieved, and the quality requirements of lens manufacturers are met.
Patent Information
- Application Number
- CN202411957053.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-29
- Publication Date
- 2025-04-04
AI Technical Summary
When the existing polythiol compositions are polymerized with isocyanate to prepare optical lenses, the lenses are often uneven in color and high defect rate, mainly because the polythiol composition contains more cyclic compound impurities.
By controlling the content of the cyclic compound in the polythiol composition, ensuring that it is less than 0.1%, and reducing the content of the cyclic compound by methods such as acid washing and high vacuum distillation, thereby preparing a high-quality polythiol composition.
The color defect rate of the lens is effectively controlled, ensuring the better softening temperature of the lens is improved, the comprehensive performance of the lens is improved, and the quality requirements of the lens manufacturer are met.
Smart Images

Figure CN119751795A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of optical materials, and in particular to a polythiol composition, a preparation method and application thereof. Background Art
[0002] Polythiourethane resin lenses are characterized by light weight, strong impact resistance, high refractive index, easy processing and dyeing. Polythiourethane optical resin materials with the above excellent properties have been an important development direction in recent years. This type of resin material is mainly prepared with polythiol compounds and isocyanates as raw materials, and sometimes cyclic compounds are used to prepare resin materials with higher refractive index.
[0003] However, the polythiol composition using polythiol compounds such as 4,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, 4,8-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, 5,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane as main components contains a large number of impurities with unknown chemical composition, which has an adverse effect on the preparation process of optical materials and the quality and performance of products. For example, when the polythiol composition is polymerized with isocyanate to prepare optical lenses, problems such as uneven lens color and high defect rate often occur. Therefore, there is an urgent need to improve the polythiol composition to overcome the above problems. Summary of the invention
[0004] In view of the problem in the prior art that lenses prepared by polymerizing a polythiol composition using polythiol compounds such as 4,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, 4,8-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, 5,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane as main components with isocyanate sometimes have the defect of uneven lens color, we conducted a comprehensive investigation and in-depth analysis and research on this problem and found that the main reason for this problem is that the polythiol composition contains a small amount of cyclic compounds, and the cyclic compounds are impurities generated by side reactions during the preparation of the polythiol composition. Through a large number of experimental investigations and studies, we determined the relationship between the cyclic compound content and the lens color defect rate, and provided a polythiol composition with a low cyclic compound content and a preparation method thereof. At the same time, the inventors found through experimental research that the resin lens prepared by the polythiol composition that does not contain any cyclic compounds has the defect of low softening temperature, which further reduces the heat resistance and causes the lens film layer to fall off or deform. Based on this, the inventors have optimized the control range of the cyclic compound content. Within this control range, the color defect rate of the lens prepared by the polythiol composition and isocyanate can be controlled within an acceptable range, while ensuring that the softening temperature of the lens is better, improving the comprehensive performance of the lens, and meeting the quality requirements of the lens production enterprise.
[0005] The present invention first provides a polythiol composition, which comprises polythiol compounds represented by formula (1), formula (2) and formula (3): Formula (1), Formula (2): Formula (3).
[0006] The mass content of the cyclic compound in the polythiol composition is ≤1.0% and is not 0, and the cyclic compound includes one or more of the compounds represented by formula (4), formula (5), formula (6), and formula (7): Formula (4), Formula (5): Formula (6): Formula (7).
[0007] Preferably, the content of cyclic compounds in the polythiol composition is ≤0.5% and is not 0.
[0008] As a further preference, the content of cyclic compounds in the polythiol composition is ≤0.1% and is not 0.
[0009] The present invention also provides a method for preparing the polythiol composition, comprising the following steps: Hydrochloric acid is added to a toluene solution of a polythiol composition containing polythiol compounds represented by formula (1), formula (2) and formula (3), and the toluene solution is acid-washed at 10-30°C for 30 minutes, twice, and degassed water is added and washed at 35-45°C for 30 minutes, five times, and toluene and trace amounts of water are removed under reduced pressure by heating, and then reduced pressure filtration is performed using a 1.2 μm PTFE membrane filter to obtain a polythiol composition.
[0010] Preferably, the mass concentration of the hydrochloric acid is 36%, the mass of the hydrochloric acid for each washing is 5-10% of the mass of the toluene solution, and the mass of the degassed water for each washing is 10-20% of the mass of the toluene solution.
[0011] The polythiol composition comprising polythiol compounds represented by formula (1), formula (2) and formula (3) is prepared by the prior art, specifically according to the technical scheme in patent CN106432664B. The inventors give the following specific steps: (1) 2-mercaptoethanol, degassed water, and sodium hydroxide aqueous solution are placed in a reactor. Epichlorohydrin is added dropwise at 9-11°C over 6.5 hours, followed by stirring to synthesize 1-chloro-3-(2-hydroxyethylthio)-2-propanol. Then, sodium sulfide aqueous solution is added dropwise at 7-37°C over 5.5 hours, followed by stirring for 120 minutes to generate a tetraol compound.
[0012] (2) Add hydrochloric acid, then add 125.8 parts by weight of thiourea, stir at 110°C for 3 hours under reflux to perform thiourea salt reaction; after cooling to 45°C, add toluene and cool to 26°C, add ammonia solution at 26°C for 30 minutes, stir at 55°C for 1 hour to perform hydrolysis reaction, and obtain a toluene solution containing polythiol compounds represented by formula (1), formula (2) and formula (3). The toluene solution contains one or more compounds represented by formula (4), formula (5), formula (6) and formula (7). The inventors can control the mass content of the above cyclic compounds to ≤1.0% and not 0 by acid washing the toluene solution at 10-30°C for 30 minutes in the above steps.
[0013] The present invention also provides a polymerizable composition, which comprises the polythiol composition, polyisocyanate and a catalyst, wherein the polythiol composition is 30-70 parts by mass, the polyisocyanate is 35-75 parts by mass, and the catalyst is 0.005-0.02 parts by mass.
[0014] The polyisocyanate may be selected from tetramethylene diisocyanate, hexamethylene diisocyanate, cyclohexane diisocyanate, 4,4'-diisocyanate dicyclohexylmethane, isophorone diisocyanate, norbornane diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, tetramethyl meta-xylylene diisocyanate, dipropyl disulfide, diethyl disulfide, 2,5-diisocyanatomethylthiophene, 2,5-diisocyanatomethyl-1,4-dithiane, 2,5 - diisocyanate-at least one of 1,4-dithiane, dihexylthiodiisocyanate, dipropylthiodiisocyanate, bis(isocyanatomethyl)adamantane, bis(isocyanatomethyl)tetrahydrothiophene, 2,6-bis(isocyanatomethyl)naphthalene, 1,5-naphthalene diisocyanate, diethylene diisocyanate, trimethylhexamethylene diisocyanate, lysine triisocyanate, toluene diisocyanate, o-tolidine diisocyanate, diphenylmethane diisocyanate, diphenyl ether diisocyanate and triphenylmethane triisocyanate.
[0015] The catalyst includes at least one of dibutyltin dilaurate, dibutyltin dichloride, dibutyltin oxide and stannous octoate.
[0016] The present invention also provides an optical resin material prepared from the polymerizable composition.
[0017] Preferably, the raw material of the optical resin material further includes a chemical auxiliary agent, and the chemical auxiliary agent is selected from at least one of a demolding agent, an ultraviolet absorber and a toner.
[0018] In order to verify the technical effect of reducing the cyclic compound impurities in this scheme, the present invention also conducted research on this. Specifically, compounds represented by formula (4), formula (5), formula (6) and formula (7) were prepared, and they were added to a polythiol composition containing only polythiol compounds represented by formula (1), formula (2) and formula (3) in different proportions. The polythiol composition was used to prepare an optical resin lens, and the lens color defect rate and softening temperature of the lens were measured. The results showed that the color defect rate of the lens was significantly correlated with the content of the cyclic compound. The higher the content of the cyclic compound, the higher the color defect rate. At the same time, as the content of the cyclic compound decreased, the softening temperature of the lens tended to decrease, especially when the content of the cyclic compound was 0, the softening temperature of the lens was significantly reduced.
[0019] The cyclic compounds represented by formula (4), formula (5), formula (6) and formula (7) used can be prepared by the following method, or can be obtained by other ways or methods. The specific preparation method is as follows: A certain amount of the polythiol composition prepared in the above scheme containing 4,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, 4,8-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane and 5,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane as the main components is taken, a certain amount of concentrated hydrochloric acid is added, the temperature is raised to above 100-120° C. and refluxed for 4-8 hours, the organic phase after the reaction is washed with water for multiple times, and then the water is removed to obtain a mixture containing the cyclic compounds represented by formula (4), formula (5), formula (6) and formula (7), and the cyclic compounds represented by formula (4), formula (5), formula (6) and formula (7) are separated and purified by high vacuum distillation.
[0020] In summary, the present invention provides a polythiol composition with a low content of cyclic compounds and a preparation method thereof, wherein the composition is used to prepare a polymerizable composition, and an optical resin material is obtained through the polymerizable composition. By controlling the content of cyclic compounds in the polythiol composition, the color defect rate of the optical resin material product is effectively controlled while other properties of the optical resin material product are maintained at the same level, while ensuring that the softening temperature of the lens is optimal, thereby improving the comprehensive performance of the lens and meeting the quality requirements of the lens manufacturer. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The mass spectrometry analysis diagram of the mixture containing the cyclic compounds of formula (4), formula (5), formula (6) and formula (7) synthesized in Experimental Example 1; Figure 2 is the H NMR spectrum of the cyclic compound of formula (4) synthesized in the experimental example; Figure 3 is the H NMR spectrum of the cyclic compound of formula (5) synthesized in the experimental example; Figure 4 is the H NMR spectrum of the cyclic compound of formula (6) synthesized in the experimental example; Figure 5 This is the hydrogen nuclear magnetic resonance spectrum of the cyclic compound of formula (7) synthesized in the experimental example. DETAILED DESCRIPTION
[0022] The technical solution of the present invention is further described below in conjunction with specific embodiments. These embodiments are only used to illustrate the technical solution of the present invention in more detail and should not be construed as limiting the protection scope of the present invention.
[0023] The 500 MHz liquid NMR spectrometer (AVANCE 500) from Bruker was used for the analysis. 1 H-NMR determination.
[0024] Agilent 6520B-QTOF liquid chromatography-mass spectrometry (LC-MS / MS) was used for mass spectrometry analysis using EI ionization method.
[0025] The method for determining the color defect rate of the lens is as follows: after the lens is trimmed, cleaned and re-cured, a colorimeter (model: UltraScan PRO) is used to measure the yellow index of 5 different positions of the lens. If the difference between the maximum and minimum values of the yellow index at different positions is ≤0.02, it is judged to be qualified; if the difference between the maximum and minimum values of the yellow index at different positions is >0.02, it is judged to be unqualified. The qualified rate is calculated by measuring a large number of lens samples (more than 100 pieces).
[0026] The fixing procedure and post-curing procedure adopted are as follows: Curing procedure: maintain at 30℃ for 180 min, heat to 45℃ after 120 min, heat to 50℃ after 90 min, heat to 60℃ after 120 min, heat to 120℃ after 240 min, maintain at 120℃ for 240 min, and cool to 70℃ after 120 min; Secondary curing procedure: maintain at 30°C for 10 min, heat to 120°C after 60 min, maintain at 120°C for 120 min, and cool to 70°C after 60 min.
[0027] Example 1 According to the method described in patent CN106432664B, a polythiol composition containing polythiol compounds represented by the above formula (1), formula (2) and formula (3) is synthesized. The specific scheme provided by the inventor is as follows: (1) 51.2 parts by weight (0.6564 mol) of 2-mercaptoethanol, 26.5 parts by weight of deaerated water (dissolved oxygen concentration 2 ppm), and 0.16 parts by weight (0.0020 mol) of a 49% aqueous sodium hydroxide solution were placed in a reactor. 61.99 parts by weight (0.6702 mol) of epichlorohydrin were added dropwise at 9 to 11°C over 6.5 hours, followed by stirring for 60 minutes to synthesize 1-chloro-3-(2-hydroxyethylthio)-2-propanol. Then, 150.0 parts by weight (0.3327 mol) of a 17.3% aqueous sodium sulfide solution were added dropwise at 7 to 37°C over 5.5 hours, followed by stirring for 120 minutes to generate a tetraol compound.
[0028] (2) 279.0 parts by weight (2.7136 mol) of hydrochloric acid having a concentration of 35.5% was added, followed by 125.8 parts by weight (1.6536 mol) of thiourea having a purity of 99.90%, and the mixture was stirred at 110° C. for 3 hours under reflux to carry out a thiourea salt reaction. After cooling to 45°C, 214.0 parts by weight of toluene were added, and the mixture was cooled to 26°C. 206.2 parts by weight (3.0323 mol) of a 25% aqueous ammonia solution were added at 26°C over 30 minutes, and the mixture was stirred at 55°C for 1 hour for hydrolysis reaction to obtain a toluene solution of polythiol with 4,8-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, 4,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane and 5,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane as main components.
[0029] (3) 59.4 parts by weight of 36% hydrochloric acid was added, and the toluene solution was acid-washed at 34°C for 30 minutes, twice. 118.7 parts by weight of deaerated water (dissolved oxygen concentration 2 ppm) was added, and the solution was washed at 35-45°C for 30 minutes, five times. Toluene and trace amounts of water were removed under reduced pressure by heating, and then the solution was filtered under reduced pressure using a 1.2 μm PTFE membrane filter to obtain a polythiol composition, which was tested to have a total cyclic compound content of 1.05%, a 4,8-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane content of 77.2%, a 4,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane content of 13.3%, a 5,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane content of 4.7%, and the remainder was irrelevant impurities.
[0030] The detection method of the cyclic compounds in the polythiol composition adopts liquid chromatography detection and uses the pure products of each component for external standard method quantification. The detection conditions of liquid chromatography are as follows: Chromatographic column: Agilent 150mm×4.6mm×4 μm Mobile phase: phosphoric acid water: acetonitrile = 45:55 (vol / vol) Column temperature: 40°C Flow rate: 1.0ml / min Detector: DAD detector, wavelength 210nm Preparation of test solution: Dissolve 45 μm sample in 1 ml of acetonitrile. Injection volume: 1 μL.
[0031] Embodiment 2-8 The polythiol composition synthesized in Example 1 undergoes a side reaction under the action of hydrochloric acid to generate cyclic compounds; the inventors changed the acid washing temperature in Example 1, and reduced the content of cyclic compounds in the polythiol composition by reducing the acid washing temperature to obtain the target composition of the present application, wherein the acid washing temperature and the corresponding cyclic compound content in step (3) of Examples 2-8 are shown in Table 1, and the other steps are the same as in Example 1. The cyclic compounds are detected by the same method as in Example 1, specifically by liquid phase quantitative detection, and a pure cyclic compound is prepared according to the following Experimental Example 1, and the pure cyclic compound is used to perform liquid phase external standard quantitative detection on the cyclic compounds in the polythiol composition.
[0032] Table 1 Pickling temperature and corresponding cyclic compound content of Examples 1-8 Example Pickling temperature Cyclic compound content% 1 34 1.05 2 30 0.86 3 28 0.63 4 25 0.42 5 22 0.19 6 18 0.10 7 15 0.04 8 10 0.02
[0033] Comparative Examples 1-4 The polythiol composition synthesized in Example 1 undergoes a side reaction under the action of hydrochloric acid to generate cyclic compounds. By increasing the acid washing temperature in Example 1, the inventors found that the content of cyclic compounds in the polythiol composition increased accordingly, and comparative examples 1-4 were obtained.
[0034] The pickling temperature and the corresponding cyclic compound content in step (3) of Comparative Examples 1-4 are shown in Table 2, and the other steps are the same as those in Example 1.
[0035] Table 2 Pickling temperature and corresponding cyclic compound content of Comparative Examples 1-4 Comparative Example Pickling temperature Cyclic compound content% 1 39 1.22 2 50 1.56 3 60 2.45 4 70 3.61
[0036] Experimental Example 1 The cyclic compounds represented by formula (4), formula (5), formula (6) and formula (7) were prepared by the following method.
[0037] (1) Into a four-necked flask equipped with a thermometer, a stirrer and a condenser, 500 g of a polythiol composition containing polythiol compounds represented by formula (1), formula (2) and formula (3) was added. The specific preparation method of the thiol composition is as described in Example 1.
[0038] (2) Add 200 g of concentrated hydrochloric acid with a mass concentration of 36%, start stirring, and heat the material temperature to 110°C through a heating jacket to react for 4 h. After completion, transfer the material to a separatory funnel, cut the lower organic phase into a four-necked flask, and add 500 g of pure water for the first stirring washing. The washing temperature is 50°C and the stirring time is 30 min. After completion, transfer the material to a separatory funnel, and transfer the lower organic phase to a four-necked flask for the second and third washings. The second and third washings are carried out in the same manner as the first washing. The obtained organic crude product is dehydrated under vacuum conditions. The dehydration temperature is 50°C, the vacuum degree is above -0.099 MPa, and the dehydration time is 180 min to obtain a mixture of cyclic compounds represented by formula (4), formula (5), formula (6), and formula (7); Afterwards, it is purified by high vacuum distillation. Under the condition of a tower top pressure of 10-15 Pa, fractions with tower top temperatures of 196-198°C, 198-200°C, 202-204°C, and 207-209°C are extracted to obtain cyclic compounds represented by formula (4), formula (5), formula (6), and formula (7), respectively.
[0039] The qualitative analysis results of the obtained products are as follows Figure 1-Figure 5 ,in Figure 1 This is the mass spectrum of the mixture of these four substances before distillation separation. Figure 2-Figure 5 They are the hydrogen nuclear magnetic resonance spectra of the cyclic compounds represented by formula (4), formula (5), formula (6) and formula (7), respectively.
[0040] Wherein, the HNMR data of the compound of formula (4) are as follows: 1H NMR: δ 2.84-2.96 (4H, 2.90 (t, J = 6.3 Hz), 2.90 (t, J = 6.3 Hz), 2.90 (t, J = 6.3 Hz), 2.90 (t, J = 6.3 Hz)), 3.00-3.11 (2H, 3.06 (d, J = 6.7Hz), 3.06 (d, J = 6.7 Hz)), 3.12-3.63 (9H, 3.17 (d, J = 6.7 Hz), 3.17 (d, J =6.7 Hz), 3.23 (ddd, J = 9.9, 4.0, 1.9 Hz), 3.25 (td, J = 10.0, 1.9 Hz), 3.28(ddd, J = 10.0, 9.7, 1.9 Hz), 3.41 (dd, J = 13.0, 10.0 Hz), 3.42 (ddd, J =9.7, 4.0, 1.9 Hz), 3.46 (dd, J = 13.0, 1.9 Hz), 3.57 (quint, J = 6.7 Hz)),3.64-3.80 (3H, 3.70 (d, J = 3.1 Hz), 3.70 (d, J = 3.1 Hz), 3.73 (dtd, J =10.0, 3.1, 1.9 Hz)). The HNMR data of the compound of formula (5) are as follows: 1H NMR: δ 2.76-2.94 (4H, 2.82 (t, J = 6.3 Hz), 2.82 (t, J = 6.3 Hz), 2.88 (t, J = 6.3 Hz), 2.88 (t, J = 6.3 Hz)), 3.00-3.62 (11H, 3.06 (d, J = 6.7Hz), 3.06 (d, J = 6.7 Hz), 3.17 (d, J = 6.7 Hz), 3.17 (d, J = 6.7 Hz), 3.23(ddd, J = 10.2, 4.0, 1.9 Hz), 3.25 (ddd, J = 10.2, 10.0, 1.9 Hz), 3.32 (ddd,J = 10.0, 9.7, 1.9 Hz), 3.40 (dd, J = 13.1, 10.0 Hz), 3.43 (ddd, J = 9.7,4.0, 1.9 Hz), 3.47 (dd, J = 13.1, 1.9 Hz), 3.56 (quint, J = 6.7 Hz)), 3.65-3.79 (3H, 3.72 (dtd, J = 10.0, 3.1, 1.9 Hz), 3.71 (d, J = 3.1 Hz), 3.71 (d, J= 3.1 Hz)). The HNMR data of the compound of formula (6) are as follows: 1H NMR: δ 2.76-2.94 (4H, 2.82 (t, J = 6.3 Hz), 2.82 (t, J = 6.3 Hz), 2.88 (t, J = 6.3 Hz), 2.88 (t, J = 6.3 Hz)), 3.02-3.24 (4H, 3.07 (d, J = 6.7Hz), 3.07 (d, J = 6.7 Hz), 3.18 (d, J = 6.7 Hz), 3.18 (d, J = 6.7 Hz)), 3.34-3.81 (9H, 3.42 (ddd, J = 13.9, 7.2, 1.8 Hz), 3.42 (dd, J = 11.3, 6.5 Hz),3.53 (ddd, J = 15.7, 7.2, 1.8 Hz), 3.56 (dd, J = 8.6, 8.2 Hz), 3.57 (ddd, J =13.9, 6.9, 1.8 Hz), 3.65 (dd, J = 11.3, 2.0 Hz), 3.65 (quint, J = 6.7 Hz), 3.73 (ddd, J = 15.7, 6.9, 1.8 Hz), 3.72 (dd, J = 8.6, 1.4 Hz)), 4.38 (1H,dddd, J = 8.2, 6.5, 2.0, 1.4 Hz). The HNMR data of the compound of formula (7) are as follows: 1H NMR: δ 2.81-2.95 (4H, 2.87 (t, J = 6.3 Hz), 2.87 (t, J = 6.3 Hz), 2.90 (t, J = 6.3 Hz), 2.90 (t, J = 6.3 Hz)), 3.00-3.15 (4H, 3.06 (d, J = 6.7Hz), 3.06 (d, J = 6.7 Hz), 3.09 (d, J = 6.7 Hz), 3.09 (d, J = 6.7 Hz)), 3.35-3.80 (9H, 3.42 (ddd, J = 13.9, 7.2, 1.8 Hz), 3.42 (dd, J = 11.1, 6.5 Hz),3.50 (ddd, J = 15.7, 7.2, 1.8 Hz), 3.58 (ddd, J = 13.9, 6.9, 1.8 Hz), 3.59 (quint, J = 6.7 Hz), 3.61 (dd, J = 8.6, 8.2 Hz), 3.63 (dd, J = 11.1, 2.0 Hz), 3.72 (ddd, J = 15.7, 6.9, 1.8 Hz), 3.71 (dd, J = 8.6, 1.4 Hz)), 4.34 (1H,dddd, J = 8.2, 6.5, 2.0, 1.4 Hz).
[0041] Experimental Example 2 The polythiol composition was synthesized with reference to a patent published by Mitsui Chemicals, Inc., with patent number CN106432664B. The synthesized polythiol composition was purified by high vacuum distillation. A high vacuum distillation device was built, the synthesized polythiol composition was added into the bottom of the tower, the vacuum pump was turned on, the absolute pressure of the distillation device was controlled below 10Pa, the temperature was raised to 260°C by oil bath, as the temperature increased, a fraction appeared at the top of the tower, the reflux ratio was controlled to 2:10, and a fraction with a top temperature of 235°C was collected. This fraction was the purified polythiol composition. Liquid quality detection showed that the polythiol composition did not contain cyclic compounds, but only contained polythiol compounds represented by formula (1), formula (2) and formula (3).
[0042] Experimental Example 3-11 The mixture of cyclic compounds represented by formula (4), formula (5), formula (6) and formula (7) prepared in Experimental Example 1 was mixed with the polythiol composition prepared in Experimental Example 2 in different proportions to obtain polythiol compositions of different compositions.
[0043] Specifically, a polythiol composition is obtained in which the mass contents of the cyclic compounds represented by formula (4), formula (5), formula (6) and formula (7) in the polythiol composition are 0.001%, 0.01%, 0.05%, 0.1%, 0.2%, 0.4%, 0.6%, 0.8% and 1.0%, respectively, and the mass ratio of formula (4), formula (5), formula (6) and formula (7) added is 1:1:1:1.
[0044] Comparative Experimental Examples 1 and 2 The polythiol composition was obtained by mixing in the same manner as in Experimental Examples 3-11, except that the mass contents of the cyclic compounds represented by formula (4), formula (5), formula (6) and formula (7) in the polythiol composition were 2.0% and 4.0%, respectively. The mass ratio of formula (4), formula (5), formula (6) and formula (7) was 1:1:1:1.
[0045] Application Experiment Example 1-9 51.2 parts by mass of xylylene diisocyanate, 0.015 parts by mass of a catalyst (dibutyltin dichloride) and 0.08 parts by mass of a release agent (polyphosphate) were added into a flask, and the mixture was stirred and dissolved at 10-15°C.
[0046] 48.8 parts by weight of the polythiol composition in Experimental Example 3-11 were added respectively, stirred evenly, and degassed with a vacuum pump. The pressure was controlled below 350 Pa and the degassing time was 1.0 hour to prepare a mixed solution. The solution was poured into a mold with a diameter of 80 mm and a center thickness of 2.0 mm, and placed in an oven for programmed temperature curing. After completion, the edge of the lens was cut off with a trimmer, cleaned and re-cured, and the color defect rate and softening temperature of the lens were measured. The results are shown in Table 3.
[0047] Application Comparative Examples 1-3 The same method as in Experimental Examples 1-9 was used to obtain lenses and to measure the color defect rate and softening temperature, except that Comparative Example 1 used the polythiol compound represented by formula (1), formula (2) and formula (3) in Experimental Example 2; Comparative Examples 2 and 3 used the polythiol compositions in Comparative Experimental Examples 1 and 2, respectively. The results are shown in Table 3. Table 3 Color defect rate detection of optical resin lenses using experimental examples 1-9 and comparative examples 1-3 Polythiol composition (parts by mass) The proportion of cyclic compounds in the polythiol composition by weight Xylylene diisocyanate (parts by mass) Lens color defect rate Softening temperature Tg Application Example 1 48.8 0.001 51.2 1 100.2 Application Example 2 48.8 0.01 51.2 2 100.3 Application Example 3 48.8 0.05 51.2 4 100.4 Application Example 4 48.8 0.1 51.2 6 100.7 Application Example 5 48.8 0.2 51.2 8 100.9 Application Example 6 48.8 0.4 51.2 9 101.1 Application Example 7 48.8 0.6 51.2 10 101.3 Application Example 8 48.8 0.8 51.2 12 101.4 Application Example 9 48.8 1.0 51.2 13 101.5 Application Comparative Example 1 48.8 0 51.2 1 98.3 Application Comparative Example 2 48.8 2.0 51.2 21 101.5 Application Comparative Example 3 48.8 4.0 51.2 37 101.7 Experimental Example 12-20 The mixture of cyclic compounds represented by formula (4), formula (5) and formula (6) prepared in Experimental Example 1 and the polythiol composition prepared in Experimental Example 2 were mixed in different proportions to obtain polythiol compositions of different compositions.
[0048] Specifically, the mass content of the cyclic compound represented by formula (4), formula (5) and formula (6) in the polythiol composition is 0.001%, 0.01%, 0.05%, 0.1%, 0.2%, 0.4%, 0.6%, 0.8% and 1.0%, respectively. The mass ratio of formula (4), formula (5) and formula (6) is 1:1:1.
[0049] Comparative Experimental Example 3-4 The polythiol composition was obtained by mixing in the same manner as in Experimental Examples 12-20, except that the mass contents of the cyclic compounds represented by Formula (4), Formula (5) and Formula (6) in the polythiol composition were 2.0% and 4.0%, respectively. The mass ratio of Formula (4), Formula (5) and Formula (6) was 1:1:1.
[0050] Application Experiment Example 10-18 The same method as in Experimental Examples 1-9 was used to obtain lenses and measure the color defect rate, except that Experimental Examples 10-18 used the polythiol compositions in Experimental Examples 12-20, respectively. The results are shown in Table 4.
[0051] Application Comparative Examples 4-5 The same method as in Experimental Examples 1-9 was used to obtain lenses and the color defect rate and softening temperature were measured. The difference was that Comparative Examples 4 and 5 used the polythiol compositions in Comparative Experimental Examples 3 and 4, respectively. The results are shown in Table 4: Table 4 Color defect rate detection of optical resin lenses using experimental examples 10-18 and comparative examples 1, 4, and 5 Polythiol composition (parts by mass) The proportion of cyclic compounds in the polythiol composition by weight Xylylene diisocyanate (parts by mass) Lens color defect rate% Softening temperature℃ Application Experiment Example 10 48.8 0.001 51.2 1 99.8 Application Experiment Example 11 48.8 0.01 51.2 2 100.1 Application Experiment Example 12 48.8 0.05 51.2 4 100.1 Application Experiment Example 13 48.8 0.1 51.2 6 100.3 Application Experiment Example 14 48.8 0.2 51.2 7 100.4 Application Experiment Example 15 48.8 0.4 51.2 9 100.6 Application Experiment Example 16 48.8 0.6 51.2 11 100.7 Application Experiment Example 17 48.8 0.8 51.2 13 101.0 Application Experiment Example 18 48.8 1.0 51.2 14 101.3 Application Comparative Example 1 48.8 0.0 51.2 1 98.3 Application Comparative Example 4 48.8 2.0 51.2 22 101.5 Application Comparative Example 5 48.8 4.0 51.2 38 101.8 The results show that the color defect rate of the lenses of Experimental Examples 10-18 is significantly lower than that of Comparative Examples 4 and 5, and the lower the content of the cyclic compound, the lower the color defect rate of the lenses, and the softening temperature also tends to decrease. The softening temperature of Comparative Example 1 is significantly lower than that of Experimental Examples 10-18.
[0052] Experimental Example 21-29 The mixture of cyclic compounds represented by formula (4) and formula (5) prepared in Experimental Example 1 was mixed with the polythiol composition containing only polythiol compounds represented by formula (1), formula (2) and formula (3) in Experimental Example 2 in different proportions to obtain polythiol compositions of different compositions.
[0053] Specifically, the mass contents of the cyclic compounds represented by formula (4) and formula (5) in the polythiol composition are 0.001%, 0.01%, 0.05%, 0.1%, 0.2%, 0.4%, 0.6%, 0.8% and 1.0%, respectively. The mass ratio of formula (4) to formula (5) is 1:1.
[0054] Comparative Experimental Example 5-6 The polythiol composition was obtained by mixing in the same manner as in Experimental Examples 21-29, except that the mass contents of the cyclic compounds represented by formula (4) and formula (5) in the polythiol composition were 2.0% and 4.0%, respectively, and the mass ratio of formula (4) to formula (5) was 1:1.
[0055] Application Experiment Example 19-27 The same method as in Experimental Examples 1-9 was used to obtain lenses and measure the color defect rate, except that Experimental Examples 19-27 used the polythiol compositions in Experimental Examples 21-29, respectively. The results are shown in Table 5.
[0056] Application Comparative Examples 6 and 7 The same method as in Experimental Examples 1-9 was used to obtain lenses and measure the color defect rate, except that Comparative Examples 6 and 7 used the polythiol compositions in Comparative Experimental Examples 5 and 6, respectively. The results are shown in Table 5; Table 5 Color defect rate detection of optical resin lenses using experimental examples 19-27 and comparative examples 1, 6, and 7 Polythiol composition (parts by mass) The proportion of cyclic compounds in the polythiol composition by weight Xylylene diisocyanate (parts by mass) Lens color defect rate Softening temperature Application Experiment Example 19 48.8 0.001 51.2 2 100.0 Application Experiment Example 20 48.8 0.01 51.2 3 100.1 Application Experiment Example 21 48.8 0.05 51.2 5 100.2 Application Experiment Example 22 48.8 0.1 51.2 7 100.4 Application Experiment Example 23 48.8 0.2 51.2 9 100.5 Application Experiment Example 24 48.8 0.4 51.2 10 100.8 Application Experiment Example 25 48.8 0.6 51.2 12 100.9 Application Experiment Example 26 48.8 0.8 51.2 14 101.2 Application Experiment Example 27 48.8 1.0 51.2 15 101.4 Application Comparative Example 1 48.8 0.0 51.2 1 98.3 Application Comparative Example 6 48.8 2.0 51.2 24 100.6 Application Comparative Example 7 48.8 4.0 51.2 40 101.8 The results show that the color defect rate of the lenses of Experimental Examples 19-27 is significantly lower than that of Comparative Examples 8 and 9, and the lower the content of the cyclic compound, the lower the color defect rate of the lenses, and the softening temperature also tends to decrease. The softening temperature of Comparative Example 1 is significantly lower than that of Experimental Examples 19-27.
[0057] Experimental Examples 30-38 The mixture of cyclic compounds represented by formula (4) prepared in Experimental Example 1 and the polythiol composition containing only polythiol compounds represented by formula (1), formula (2) and formula (3) in Experimental Example 2 were mixed in different proportions to obtain polythiol compositions of different compositions.
[0058] Specifically, the obtained polythiol compositions have mass contents of the cyclic compound represented by formula (4) in the polythiol composition of 0.001%, 0.01%, 0.05%, 0.1%, 0.2%, 0.4%, 0.6%, 0.8% and 1.0%, respectively.
[0059] Comparative Experimental Examples 7-8 The polythiol composition was obtained by mixing in the same manner as in Experimental Examples 30-38, except that the mass contents of the cyclic compound represented by formula (4) in the polythiol composition were 2.0% and 4.0%, respectively.
[0060] Application Experiment Example 28-36 The same method as in Experimental Examples 1-9 was used to obtain lenses and measure the color defect rate, except that Experimental Examples 28-36 used the polythiol compositions in Experimental Examples 30-38, respectively. The results are shown in Table 6.
[0061] Application Comparative Examples 8 and 9 The same method as in Experimental Examples 1-9 was used to obtain lenses and measure the color defect rate, except that Comparative Examples 8 and 9 used the polythiol compositions in Comparative Experimental Examples 7 and 8, respectively. The results are shown in Table 6. Table 6 Color defect rate detection of optical resin lenses using experimental examples 28-36 and comparative examples 1, 8, and 9 Polythiol composition (parts by mass) The proportion of cyclic compounds in the polythiol composition by weight Xylylene diisocyanate (parts by mass) Lens color defect rate Softening temperature Application Experiment Example 28 48.8 0.001 51.2 2 99.9 Application Experiment Example 29 48.8 0.01 51.2 3 100.0 Application Experiment Example 30 48.8 0.05 51.2 5 100.2 Application Experiment Example 31 48.8 0.1 51.2 7 100.3 Application Experiment Example 32 48.8 0.2 51.2 8 100.5 Application Experiment Example 33 48.8 0.4 51.2 10 100.8 Application Experiment Example 34 48.8 0.6 51.2 11 100.9 Application Experiment Example 35 48.8 0.8 51.2 12 101.1 Application Experiment Example 36 48.8 1.0 51.2 14 101.3 Application Comparative Example 1 48.8 0.0 51.2 1 98.3 Application Comparative Example 8 48.8 2.0 51.2 23 101.5 Application Comparative Example 9 48.8 4.0 51.2 39 101.7 The results show that the color defect rate of the lenses of Experimental Examples 28-36 is significantly lower than that of Comparative Examples 8 and 9, and the lower the content of the cyclic compound, the lower the color defect rate of the lenses, and the softening temperature also tends to decrease. The softening temperature of Comparative Example 1 is significantly lower than that of Experimental Examples 28-36.
[0062] The data of the above application experimental examples and application comparative examples fully prove that the inventor can control the color defect rate of the lens prepared by the polythiol composition and isocyanate within an acceptable range by controlling the content range of the cyclic compound, while ensuring that the softening temperature of the lens is better, improving the comprehensive performance of the lens, and meeting the quality requirements of the lens manufacturing company; while the resin lens prepared by the polythiol composition that does not contain any cyclic compound has the defect of low softening temperature, which further reduces the heat resistance and causes the lens film layer to fall off or deform. Therefore, the technical solution of the present application is the best solution to solve the defects of the prior art.
[0063] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any equivalent substitutions, modifications, etc. made by technicians in this field without any creative work within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A polythiol composition comprising polythiol compounds represented by formula (1), formula (2) and formula (3), Formula (1), Formula (2): Formula (3), It is characterized in that The polythiol composition further contains a cyclic compound, the mass content of which is 0<≤1.0%, and the cyclic compound is selected from one or more compounds represented by formula (4), formula (5), formula (6), and formula (7); Formula (4), Formula (5): Formula (6): Formula (7).
2. The polythiol composition according to claim 1, characterized in that The mass content of cyclic compounds in the polythiol composition is ≤0.5% and is not 0.
3. The polythiol composition according to claim 1, characterized in that The mass content of cyclic compounds in the polythiol composition is ≤0.1% and is not 0.
4. The method for preparing the polythiol composition according to any one of claims 1 to 3, characterized in that: The following steps are involved: To a toluene solution of a polythiol composition comprising polythiol compounds represented by formula (1), formula (2) and formula (3), hydrochloric acid is added, and the toluene solution is acid-washed at 10-30°C for 30 minutes, twice; then, degassed water is added, and washing is performed at 35-45°C for 30 minutes, five times; toluene and trace amounts of water are removed under reduced pressure by heating, and then reduced pressure filtration is performed using a 1.2 μm PTFE membrane filter to obtain a polythiol composition.
5. The preparation method according to claim 4, characterized in that: The mass concentration of the hydrochloric acid is 36%, the mass of the hydrochloric acid for each washing is 5-10% of the mass of the toluene solution, and the mass of the degassed water for each washing is 10-20% of the mass of the toluene solution.
6. A polymerizable composition, characterized in that The polymerizable composition comprises the polythiol composition according to any one of claims 1 to 3, a polyisocyanate and a catalyst, wherein the polythiol composition is 30-70 parts by mass, the polyisocyanate is 35-75 parts by mass, and the catalyst is 0.005-0.02 parts by mass.
7. The polymerizable composition according to claim 6, characterized in that: The polyisocyanate is specifically selected from tetramethylene diisocyanate, hexamethylene diisocyanate, cyclohexane diisocyanate, 4,4'-diisocyanate dicyclohexylmethane, isophorone diisocyanate, norbornane diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, tetramethyl-m-xylylene diisocyanate, dipropyl disulfide, diethyl disulfide, 2,5-diisocyanatomethylthiophene, 2,5-diisocyanatomethyl-1,4-dithiane, 2,5-diisocyanatomethyl-1,4-dithiane, At least one of isocyanate-1,4-dithiane, dihexylthiodiisocyanate, dipropylthiodiisocyanate, bis(isocyanatomethyl)adamantane, bis(isocyanatomethyl)tetrahydrothiophene, 2,6-bis(isocyanatomethyl)naphthalene, 1,5-naphthalene diisocyanate, diethylene diisocyanate, trimethylhexamethylene diisocyanate, lysine triisocyanate, toluene diisocyanate, o-tolidine diisocyanate, diphenylmethane diisocyanate, diphenyl ether diisocyanate and triphenylmethane triisocyanate.
8. The polymerizable composition according to claim 6, characterized in that: The catalyst includes at least one of dibutyltin dilaurate, dibutyltin dichloride, dibutyltin oxide and stannous octoate.
9. An optical resin material prepared from the polymerizable composition according to any one of claims 6 to 8.
Citation Information
Patent Citations
Methods for manufacturing polythiol compounds, polymeric compositions for optical materials and their uses
CN106432664B
Cited By
Preparation method of bis (mercaptomethyl)-3, 6, 9-trithia-n-undecane-1, 11-dimercaptoalcohol and modified polyurethane optical material raw material composition containing bis (mercaptomethyl)-3, 6, 9-trithia-n-undecane-1, 11-dimercaptoalcohol
CN121021348A